Effect of attention bias modification on brain function and anxiety in patients with irritable bowel syndrome: A preliminary electroencephalogram and psycho‐behavioral study. Issue 12 (14th June 2017) - Tayama, J.; Saigo, T.; Ogawa, S.; Takeoka, A.; Hamaguchi, T.; Hayashida, M.; Fukudo, S.; Shirabe, S.
Abstract: Background: Gastrointestinal symptoms of irritable bowel syndrome (IBS) show a reciprocal relationship with anxiety. In this intervention‐based study, we investigated the utility of attention bias modification (ABM) therapy in patients with IBS. We hypothesized that IBS‐related electroencephalographic abnormalities would be normalized after ABM therapy. Methods: Seventeen patients with IBS and 13 healthy subjects completed five ABM intervention sessions over a 2‐month period. Each session included 128 ABM trials, resulting in a total of 640 trials across the intervention period. For each trial, subjects viewed a pair of facial expression images and were instructed to indicate the position of the neutral face as quickly and accurately as possible by pressing one of two buttons on a button box. Electroencephalography data (alpha and beta power percentages) were collected during the 1st and 5th sessions. Key Results: Generalized estimating equations of relative alpha power revealed a significant effect of period was identified at O2 ( P =.036). Paired t tests revealed that ABM significantly increased relative alpha power at O2 in patients with IBS. Generalized estimating equation of relative beta power revealed a significant effect of the group × period interaction was identified at Pz ( P =.035). Paired t tests revealed that ABM significantly decreased relative beta power at Pz in patients with IBS. Conclusions & Inferences: Attention bias modification may normalize brain function related to attention and anxiety in patients with IBS. Abstract : We hypothesized that attention bias modification (ABM) would lead to generalized whole‐brain increases in alpha power percentage and decreases in beta power percentage of electroencephalogram in patients with IBS. Alpha and beta power percentages were normalized after ABM at parietal and right occipital regions in the IBS group. ABM may normalize brain function related to attention and anxiety in patients with IBS.